Project Maturity of Regional Airports in Poland as a Degree of Project Management: The Results of Empirical Studies - Magdalena DOLATA; Anna CHWIŁKOWSKA-KUBALA (Communications of International Proceedings, 2021)
Dynamic changes taking place in the environment create new quality conditions for the functioning of the organization, forcing the need to remodel the organizational solutions used. In such a broad reality, projects become a key element which conditions the efficiency of undertaken activities in the organization. As a result of the increase in the number of projects carried out in virtually every industry and the popularization of project management methods in organizations, there is a need to assess the degree of advancement of project management, reflected by individual levels of project maturity of the organization. As a result of the observations made, the aim of the article was to join the discussion on the project maturity of the organization in Polish regional airports. The article consists of two main parts. In the first part, the starting point is the presentation of the essence of the organization's project maturity and the importance of its research from the perspective of the organization. Then the article refers to the specificity of airport management in Poland, taking into account the projects carried out in them. The second part of the paper discusses the results of the research on the design maturity of organizations in Polish airports. The considerations presented in the article refer to the results of the research proceedings conducted in the first half of 2020.
Keywords: Project Maturity; Project Management; Regional Airport Management.